(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The encapsulation rates recorded for four species of mealybugs, when attacked by some of their principal and accidental encyrtid parasitoids, were studied under controlled conditions in no-choice assays. The encapsulation intensity was measured as effective encapsulation (EE) a value representing the percentage of parasitized mealybugs that encapsulated all parasitoid eggs and therefore prevented parasitoid development; and as aggregate encapsulation (AE) a value representing the percentage of eggs encapsulated. None or low rates (up to 12%) of EE by Planococcus citri (Risso), P. ficus (Signoret), and Pseudococcus longispinus (Tagioni-Tozzetti) were recorded when parasitization was conducted by principal parasitoids. Parasitization of P. citri, P. longispinus and Pseudococcus viburni (Signoret) by accidental parasitoids was characterized by high rates of AE and EE (86-100% for both values), suggesting that these mealybug species are unsuitable for the development of these parasitoids. The effects of cross parasitization of allopatric and sympatric ecotypes on the encapsulation values were investigated with P. citri and A. pseudococci, from Israel, Portugal and Sicily. EE was affected by the ecotype of both the host and the parasitoid. Thus, the lowest (17%) and the highest (70%) EE were recorded when Portuguese and Sicilian of P. citri, respectively, were attacked by the Israeli A. pseudococci. Increasing egg load (superparasitism) was evident for several of the tested parasitoids when they attacked unsuitable hosts. When P. citri was attacked by A. pseudococci, EE values for superparasitized hosts were much lower than for solitary parasitized hosts. It is suggested that this oviposition strategy aims at reducing values of EE, thereby increasing offspring survival.